Anaemia among primary care patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD): a multicentred cross-sectional study. Issue 12 (22nd December 2018) - Idris, Iliza; Tohid, Hizlinda; Muhammad, Noor Azimah; A Rashid, Mohd Radzniwan; Mohd Ahad, Azainorsuzila; Ali, Norsiah; Sharifuddin, Naemah; Aris, Junita Harizon
Abstract : Objectives: This study aimed to determine the prevalence of anaemia among patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) at primary care settings and its associated factors. Design, setting and participants: This cross-sectional study involved 808 adult patients with T2DM and CKD who were recruited via systematic sampling from 20 public primary care clinics in Peninsular Malaysia. Their sociodemographic, clinical and biomedical profiles were collected through interviews, examination of medical records and blood testing. Results: The prevalence of anaemia was 31.7% (256/808). The anaemia was mainly mild (61.5%) and normocytic normochromic (58.7%). About 88.7% of the patients with anaemia were not known to have anaemia prior to the study. Among 36 patients with documented history of anaemia, 80.6% were still anaemic, and only a half received iron therapy. Multivariate regression analysis showed that women (adjusted odd ratio (AOR): 1.57, 95% CI: 1.12 to 2.21, p=0.009) and those with older age (AOR: 1.04, 95% CI: 1.01 to 1.06, p<0.001), CKD stage 3a (AOR: 2.47; 95% CI: 1.25 to 4.87, p=0.009), CKD stage 3b (AOR: 4.36; 95% CI: 2.14 to 8.85, p<0.001), CKD stage 4 (AOR: 10.12; 95% CI: 4.36 to 23.47, p<0.001), CKD stage 5 (AOR: 10.80; 95% CI: 3.32 to 35.11, p<0.001) and foot complication (AOR 3.12, 95% CI: 1.51 to 6.46, p=0.002) were more likely to have anaemia. Having higher body mass index (AOR 0.95, 95% CI: 0.92 to 0.99, p=0.012) and higher diastolic blood pressure (AOR 0.97, 95% CI: 0.95 to 0.99, p<0.001) were associated with lower odds to have anaemia. Conclusion: Anaemia among patients with T2DM and CKD in primary care was common, and the majority was unrecognised. Inadequate treatment of anaemia was also prevalent. Therefore, screening of anaemia should be incorporated into the routine assessment of diabetic complications particularly for those with significant associated factors. It is hoped that such strategy could lead to early treatment and hence improve their overall care. Trial registration number: NMRR-15-660-24324.